Village Apparatus Competency Development Model Based on Government and Developmental Needs (Study in Labuan District and Muncang District) - Rajab, Ridwan; Tumanggor, Budi Fernando; Gaol, Porman Lumban (KnE Social Sciences, 2025)
This research is qualitative and compares how the implementation of the village apparatus competency development model system is in accordance with the needs of government and development, and will use supporting data related to the assessment of the Village Development Index system issued by the Ministry of Villages, Disadvantaged Regions and Transmigration. There is a lack of discipline in reporting village development or village officials who have participated in and completed ASN development. So there is no data on the distribution of village apparatus competencies to be monitored or to organize knowledge sharing activities between village officials. Moreover, so far in Muncang District, there has been no data on village apparatus competency and only received it ready-made or instant. In Labuan District, the budget has not supported village apparatus development or has not been a priority. The village head of Labuan District considers sub-district revitalization to be an urgent matter in the Labuan District regional government program. So it is necessary to create a legal umbrella related to budget disbursement to monitoring activities in the regional government, especially sub-districts or villages.